RANCANG BANGUN SISTEM INFORMASI KELAS KREATIF BERBASIS WEBSITE (STUDI KASUS : SEKARANG CREATIVE CLASS) - Abelia, Adinda; Wicaksono, Soetam Rizky (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2025)
The Creative Class Information System is designed to simplify class management activities, including recording data for mentors, affiliations, materials, suppliers, schedules, venues, and participants. This integrated system features payment and material purchase transactions, streamlining administrative processes. With an organized database structure, the system ensures efficient and secure data storage. The web-based platform allows broader and more flexible access for users, including admins, mentors, and participants. The system's development aims to enhance class operational efficiency and provide a better experience for all stakeholders involved.